1998
DOI: 10.1111/j.1471-0528.1998.tb10007.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of medical and surgical termination of pregnancy: choice, emotional impact and satisfaction with care

Abstract: Objective To investigate whether women having medical or surgical terminations of pregnancy differ in their emotional distress before or after the procedure. To evaluate whether choice of procedure occurs, the factors influencing type of procedure and the effect of choice on emotional responses and satisfaction with care.Design A prospective comparative study. Setting A termination of pregnancy unit in a University Teaching Hospital. Participants Two hundred and seventy-five women attending for medical or surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 22 publications
4
58
1
1
Order By: Relevance
“…26,85,86,93 Consistent with prior randomised trials 26,93 and cohort studies 85,86,94,95 that have used HADS or EPDS as a means of screening for anxiety and depression, we found no difference in mean scores between women having MTOP and STOP. The proportion of 'clinical' cases of anxiety and depression during the first month after abortion (inferred, for example, by the proportion of women with HADS > 10) has also been found to be similar in women having MTOP and STOP (6-28% for anxiety and 2-10% for depression).…”
Section: Psychological Outcomesupporting
confidence: 74%
See 2 more Smart Citations
“…26,85,86,93 Consistent with prior randomised trials 26,93 and cohort studies 85,86,94,95 that have used HADS or EPDS as a means of screening for anxiety and depression, we found no difference in mean scores between women having MTOP and STOP. The proportion of 'clinical' cases of anxiety and depression during the first month after abortion (inferred, for example, by the proportion of women with HADS > 10) has also been found to be similar in women having MTOP and STOP (6-28% for anxiety and 2-10% for depression).…”
Section: Psychological Outcomesupporting
confidence: 74%
“…Women were less satisfied with the technical and interpersonal aspects of care, but not the waiting time for MTOP. Although satisfaction data were not reported in previous randomised trials, two cohort studies comparing MTOP and STOP have measured overall satisfaction with care; Slade et al 86 found no difference in mean scores on the Satisfaction with Care Scale, but Jensen et al, 24 using a 5-point scale, reported higher mean satisfaction scores with STOP. Taken together the results of the present study and those of most prior studies suggest that experiences of care are more negative and satisfaction lower with MTOP, likely contributing to the lower acceptability of medical abortion prior to 14 weeks of pregnancy.…”
Section: Semantic Rating/satisfactionmentioning
confidence: 86%
See 1 more Smart Citation
“…The difficulties obtaining follow-up data on women after abortion have been highlighted previously, with response rates typically between 60% and 75% within the 4 weeks after the procedure, falling to as low as 30% thereafter. 18,26,27,86,97,100 …”
Section: Limitations Of Researchmentioning
confidence: 99%
“…Although women state both methods of termination are acceptable 6 , some findings suggest that not all women played a part in the decision making about treatment option and/or felt they had a choice on the abortion method 7 . Few, if any, studies have documented the information women receive prior to their decision making about abortion method 3,11 .…”
Section: Introductionmentioning
confidence: 99%